Comparative analysis of ambient, in-home, and personal exposures reveals associations between breathing zone pollutant levels and asthma exacerbations in high-risk children - Camille M. Moore; Jonathan Thornburg; Elizabeth A. Secor; Katharine L. Hamlington; Allison M. Schiltz; Kristy L. Freeman; Jamie L. Everman; Tasha E. Fingerlin; Andrew H. Liu; Max A. Seibold (Respiratory Research, 2025)
Abstract Background Air pollution is associated with poor asthma outcomes in children. However, most studies focus on ambient or indoor monitor pollution levels. Few studies evaluate breathing zone exposures, which may be more consequential for asthma outcomes. Methods We measured personal exposures to NO2, O3, PM10 and PM10 constituents, including black carbon (BC), brown carbon (BrC), environmental tobacco smoke (ETS), endotoxins, and 𝛽-glucan, in a cohort of children with exacerbation-prone asthma for 72 h using wearable monitors. Personal exposures were compared to concentrations from in-home monitors in the child’s bedroom and ambient EPA air quality monitoring using correlation analyses. Personal exposures were tested for association with lung function and compared between participants with and without well-controlled asthma and signs of exacerbation in the prior 60 days using censored regression with robust standard errors. Results 81 children completed 219 monitoring sessions. Personal NO2, O3, and PM10 exposures ranged from < 2 to 99.1 parts per billion (ppb), < 1.5 to 23.3 ppb, and < 1 to 141.9 𝜇g/m3, respectively. Personal endotoxin ranged from 0.04 to 101.3 EU/m3, 𝛽-glucan from 18.5 to 1,162 pg/m3, BC from < 0.3 to 46.9 𝜇g/m3, BrC from < 0.3 to 6.1 𝜇g/m3, and ETS from < 0.3 to 56.6 𝜇g/m3. Correlations between personal and ambient PM10, NO2, and O3 concentrations were poor, whereas personal PM10 and NO2 correlated with in-home concentrations. In-home monitoring less frequently detected BrC (Personal:79% > lower limit of detection, Home:36.8%) and ETS (Personal:83.7%, Home:4.1%) than personal exposures, and detected BC in participants without personal exposure (Personal: 26.5%, Home: 96%). Personal exposures were not significantly associated with lung function or daily asthma control. Children requiring corticosteroid treatment for asthma exacerbation within 60 days of exposure monitoring had 1.98, 2.21 and 2.04 times higher personal exposures to BrC (p < 0.001; 95% CI: 1.43–2.37), ETS (p = 0.007; 95% CI: 1.25–3.91), and endotoxin (p = 0.012; 95% CI: 1.14–3.68), respectively. Conclusions Although in-home monitoring was correlated with personal exposure to PM10 and NO2, in-home detection of ETS and BrC was not associated with personal exposures. Personal PM10 exposures in general, as well as BrC, ETS, and endotoxin levels were associated with recent childhood asthma exacerbations. Clinical trial number Not applicable.